Novel Pre- and Postoperative Care Using Telemedicine - Ferrari-Light, Dana; Geraci, Travis C.; Chang, Stephanie H.; Cerfolio, Robert J. (Frontiers in Surgery, 2020)
The use of telemedicine and telehealth services has grown exponentially over the past decade and has become increasingly relevant and necessary during the Coronavirus Disease 2019 (COVID-19) pandemic. There remains ample opportunity to electronically connect cardiothoracic surgeons with their patients during both preoperative and postoperative visits. In this review, we examine the various implementations of telemedicine within thoracic surgery and explore future applications in this quickly developing field.